Dynamic Dazzle Distorts Speed Perception. - Joanna R Hall; Innes C Cuthill; Roland Baddeley; Angela S Attwood; Marcus R Munafò; Nicholas E Scott-Samuel (PLoS ONE)
Static high contrast ('dazzle') patterns, such as zigzags, have been shown to reduce the perceived speed of an object. It has not escaped our notice that this effect has possible military applications and here we report a series of experiments on humans, designed to establish whether dynamic dazzle patterns can cause distortions of perceived speed sufficient to provide effective defence in the field, and the extent to which these effects are robust to a battery of manipulations. Dynamic stripe patterns moving in the same direction as the target are found to increase the perceived speed of that target, whilst dynamic stripes moving in the opposite direction to the target reduce the perceived speed. We establish the optimum position for such dazzle patches; confirm that reduced contrast and the addition of colour do not affect the performance of the dynamic dazzle, and finally, using the CO2 challenge, show that the effect is robust to stressful conditions.